In Vivo and In Vitro Protein Phosphorylation Studies on Ochromonas danica, an Alga with a Chlorophyll a/c/Fucoxanthin Binding Protein - Gibbs, Pamela B. (1991)
The phosphorylation of thylakoid membranes in the Chromophyte alga Ochromonas danica was studied in whole cells and in vitro. Protein kinase activity was observed in the thylakoid fraction, and several membrane-bound polypeptides were found to be phosphorylated. The thylakoid protein kinase demonstrated several unusual regulatory properties. Both the polypeptides that were phosphorylated and the rate of protein phosphorylation were independent of illumination. Protein kinase activity was also unaffected by 3-(3,4-dichlorophenyl)-1,1-dimethylurea, diuron. The kinase activity was inhibited under strong reducing conditions. Whole cells labeled with (32)PO(4)(3−) were converted to light states I and II by pre-illumination favoring photosystem I or photosystem II, respectively. Analysis of the phosphoproteins from cells in state I and state II showed that no changes in phosphorylation accompanied the change in energy redistribution.